Reproductive biology of the South American endemic hermit crab Isocheles sawayai (Crustacea, Anomura) from the Southern coast of Brazil - Stanski, Gilson [UNESP] (2016)
The goal of this study was to investigate the sex ratio, structure and reproductive biology of Isocheles sawayai, a hermit crab captured as bycatch in a non-selective shrimp fishery. The animals were collected from July 2010 to June 2011. Out of the 575 individuals found, the majority were concentrated near the coast with a predominance of silt and clay in the sediment and warmer water. The mean length of males was 7.5 mm, which was larger than that of females (5.5 mm). The sex ratios were male-biased, except in November. The reproductive period was seasonal, with a peak during the spring, mainly in November, when 95% of the total ovigerous females were recorded. Our results suggest different habitat preferences exist according to sex; males prefer coastal regions and females prefer intertidal zones. However, the data demonstrated that both sexes utilised the same coastal regions in the reproductive period, mainly in November. A higher intensity of rainfall was observed in the spring (October, November and December), and early summer, which probably promotes the transport of coastal organic materials, and creates an excellent environment for the reproduction and subsequent larval development of benthic animals such as I. sawayai.